2022
DOI: 10.1002/cpp.2785
|View full text |Cite
|
Sign up to set email alerts
|

Sensory processing in depression: Assessment and intervention perspective

Abstract: Few studies have examined sensory processing in mood disorders, including depression. The interactions between sensory inputs and adaptive behaviour have yet to be clarified in this pathology. We assessed sensory profiles among people with major depressive disorder (MDD) with the Adult/Adolescent Sensory Profile scale and determined whether sensory processing patterns were associated with clinical variables such as anxiety, depression, psychomotor retardation or self‐esteem. We compared 25 participants with MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…This finding has been reported in the literature even in individuals without a diagnosis of autism spectrum disorder or other neurodevelopmental disorders (Cervin, M., 2023, andConelea, Carter &Freeman, 2014). Paquet et al (2022) found that high levels of sensory processing difficulties are associated with symptoms of anxiety, depression, and low self-esteem. Difficulties in sensory processing, both excessive and deficient, are also linked to lower performance in daily life tasks, even in the absence of cognitive disabilities.…”
Section: Discussionsupporting
confidence: 80%
“…This finding has been reported in the literature even in individuals without a diagnosis of autism spectrum disorder or other neurodevelopmental disorders (Cervin, M., 2023, andConelea, Carter &Freeman, 2014). Paquet et al (2022) found that high levels of sensory processing difficulties are associated with symptoms of anxiety, depression, and low self-esteem. Difficulties in sensory processing, both excessive and deficient, are also linked to lower performance in daily life tasks, even in the absence of cognitive disabilities.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, individuals with schizophrenia, bipolar disorder, and ASD yield higher sensory avoidance scores than those with typical development. Patients with depression also exhibit extreme sensory processing patterns that are higher in all four quadrants compared to healthy controls, and this has been found to be associated with depressive symptoms, including anxiety (Paquet et al, 2022). A study examining the effect of differences in sensory processing patterns on children’s participation in leisure activities found that avoidance scores were negatively correlated with a preference for social activities (Ismael et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sensory processing disorders have been described in people with depression and might be a trait of individuals suffering from major depression (Engel‐Yeger et al, 2018 ). In the article of Paquet et al ( 2022 ), it was investigated whether sensory profiles assessed with the Adult/Adolescent Sensory Profile Scale among French patients with Major Depressive Disorder were associated with anxiety, depression, psychomotor retardation or self‐esteem. Results revealed that extreme sensory processing patterns emerged among patients suffering from Major Depressive Disorder.…”
Section: Introductionmentioning
confidence: 99%